2022
DOI: 10.48550/arxiv.2201.04089
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tracing pebble drift and trapping using radial carbon depletion profiles in protoplanetary disks

J. A. Sturm,
M. K. McClure,
D. Harsono
et al.

Abstract: Context. The composition of planets may be largely determined by the chemical processing and accretion of icy pebbles in protoplanetary disks. Recent observations of protoplanetary disks hint at wide-spread depletion of gaseous carbon. The missing volatile carbon is likely frozen in CO and/or CO 2 ice on grains and locked into the disk through pebble trapping in pressure bumps or planetesimals. Aims. We aim to measure the total elemental C/H ratio in the outer region of seven disks, four of which have been pre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 84 publications
1
5
0
Order By: Relevance
“…Interestingly enough, the CO-HD discrepancy is not there for warmer disks around Herbig stars (Kama et al 2020), supporting the idea of volatile lock-up happening when freeze-out is more efficient. A similar trend between C depletion and disk temperature has been recently found with [CI] Atacama Compact Array (ACA) observations by Sturm et al (2022).…”
Section: Gas Mass From Hd Emission -supporting
confidence: 86%
“…Interestingly enough, the CO-HD discrepancy is not there for warmer disks around Herbig stars (Kama et al 2020), supporting the idea of volatile lock-up happening when freeze-out is more efficient. A similar trend between C depletion and disk temperature has been recently found with [CI] Atacama Compact Array (ACA) observations by Sturm et al (2022).…”
Section: Gas Mass From Hd Emission -supporting
confidence: 86%
“…This could be the case if the material originated from within the protoplanetary disks because the gas-to-dust and 12 CO:H 2 ratios in disks are both expected to decrease over time (e.g., Gorti et al 2015;Miotello et al 2019). Sturm et al (2022) find evidence from [C I] observations that carbon is depleted by a factor of 17 from ISM levels in the outer regions of the DO Tau disk, which would in turn reduce the 12 CO:H 2 ratio. Wide-field observations with better uv coverage will be necessary to robustly examine the consistency between the 13 CO-derived mass and the Herschel-derived mass.…”
Section: Mass Constraints On Structures Surrounding Do Taumentioning
confidence: 99%
“…It will also be useful to improve constraints on DO Tau's C/O ratio, which is expected to increase between the Class I and II stages (e.g., Cleeves et al 2018;Miotello et al 2019). Results have thus far been mixed; Sturm et al (2022) derived a relatively high C/O ratio of ∼1 based on spatially unresolved [C I] observations but found that the C 2 H upper limit from Bergner et al (2019) was better explained by an ISM-like ratio of 0.47. Obtaining deeper and higher resolutions of [C I] and C 2 H, or estimating the C/O ratio from SO/CS, can help to resolve this ambiguity.…”
Section: Avenues For Clarifying the Origins Of Do Tau's Extended Stru...mentioning
confidence: 99%
“…This could be the case if the material originated from within the protoplanetary disks, since the gas-to-dust and 12 CO:H 2 ratios in disks are both expected to decrease over time (e.g., Gorti et al 2015;Miotello et al 2019). Sturm et al (2022) find evidence from [C I] observations that carbon is depleted by a factor of 17 from ISM levels in the outer regions of the DO Tau disk, which would in turn reduce the 12 CO:H 2 ratio. Widefield observations with better uv coverage will be necessary to robustly examine the consistency between the 13 CO-derived mass and the Herschel-derived mass.…”
Section: Mass Constraints On Structures Surrounding Do Taumentioning
confidence: 99%
“…It will also be useful to improve constraints on DO Tau's C/O ratio, which is expected to decrease between the Class I and II stages (e.g., Cleeves et al 2018;Miotello et al 2019). Results have thus far been mixed; Sturm et al (2022) derived a relatively high C/O ratio of ∼ 1 based on spatially unresolved [C I]] obervations but found that the C 2 H upper limit from Bergner et al (2019) was better explained by an ISM-like ratio of 0.47. Obtaining deeper and higher resolutions of [C I] and C 2 H, or estimating the C/O ratio from SO/CS, can help to resolve this ambiguity.…”
Section: Evidence For Remnant Envelope Materialsmentioning
confidence: 99%